Co-gasification of oil palm biomass in a pilot scale downdraft gasifier - Anyaoha, Kelechi E.; Sakrabani, Ruben; Patchigolla, Kumar; Mouazen, Abdul M. (Elsevier, 2020)
The present study focused on co-gasification of empty fruit bunch (EFB), mesocarp fibre (MF) and palm kernel shell (PKS) in a 75 kWth pilot scale downdraft gasifier for possible synergic reactions between the biomass. A series of experiments was carried out using equal blend of EFB, MF, and PKS (particle sizes of 14 and 6.7 mm) and equal blend of MF and PKS. Advanced infrared multi-gas analyser, and thermal conductivity gas analyser were employed to measure the produced gases. The elemental compositions of the raw biomass, ash and slag generated were determined using Scanning Field Emission Gun Scanning Electron Microscopy with accelerating voltage 20.0 kV and working distance 6 mm and the measurements processed using AztecEnergy V2.2 software. The co-gasification of blend of EFB, MF, and PKS, compared to the blend of MF and PKS led to higher gas yield (4.82 and 3.47 m3/kg_biomass), cold gas efficiency (16.2 and 13.37%), and carbon conversion efficiency (56.3 and 34.18%), respectively. When compared to particle size of 14 mm, the PKS of particle size of 6.7 mm in the EFB/MF/PKS blend increased the lower heating value and the higher heating value of the producer gas by 20% and 20.3%, respectively, and the residue yield was 18.6% less. The overall result has provided evidence on the importance of co-gasification of biomass especially EFB, MF and PKS, which will result in increased utilization of EFB.
Keywords: Empty fruit bunch; Palm kernel shell; Mesocarp fibre; Co-gasification